Internet use among young adults in the Philippines an inter-leisure demand analysis - Panti, Rene Marlon; Kraft, Aleli D. (Quezon City School of Economics, University of the Philippines Diliman, 2019)
With the important implications of the prevalence of internet use and the continual rise in the time allocated for it, I investigate the factors that affect its demand and measure the probability of displacement that it causes other leisure activities. I use the Young Adult Fertility Survey 4 as the main source of data and categorize leisure into five general activities namely internet use, traditional media use, reading, exercise, and sleep. I find that the use of internet is significantly influenced by factors affecting skill and access namely age, educational attainment, level of urbanity, internet access at home, type of school the individual currently attends, civil status, family size, and number of friends. I also find that income variables and the availability of capital goods are significantly related to being online. In terms of displacement at low levels of internet use, I find that sleep is the most vulnerable and online engagement appears to complement use of traditional media. At higher levels of internet use, displacement occurs to almost all possible leisure combinations. Sleep still has the highest probability of being displaced but online engagement becomes a substitute to traditional media use.
Thesis (M.A. Economics) -- University of the Philippines Diliman
Keywords: Internet users -- Philippines; Young adults -- Philippines; Leisure -- Economic aspects -- Philippines